If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 13r + 4 + -7r = 0 Reorder the terms: 4 + 13r + -7r = 0 Combine like terms: 13r + -7r = 6r 4 + 6r = 0 Solving 4 + 6r = 0 Solving for variable 'r'. Move all terms containing r to the left, all other terms to the right. Add '-4' to each side of the equation. 4 + -4 + 6r = 0 + -4 Combine like terms: 4 + -4 = 0 0 + 6r = 0 + -4 6r = 0 + -4 Combine like terms: 0 + -4 = -4 6r = -4 Divide each side by '6'. r = -0.6666666667 Simplifying r = -0.6666666667
| -2+ln(x-4)=4 | | 5x+10x+5=25 | | 5x+10x+5=25 | | 5x+10x+5=25 | | 2B-6=4B | | 3-(3x-8)=4y-5 | | (4c-6c+5)(4c-2c-1)= | | lnx-2lnx=3 | | 6x-4=20x+3 | | 6x-23+x+54=180 | | 4x+2x(x+4)= | | -4x-6(-2+4)=64 | | 2x+y-z=7z | | -4x-6(-2+4)=64 | | 3x-1=-3x+3 | | 3x-1=-3x+3 | | -5x+-2=-2X+4 | | -6x-5(-3x-3)=60 | | 114=2x+3x | | 5x+7y=3890 | | 8x+7y-5-5x+6y-3= | | -2x-2(-5x-4)=-80 | | 15+4y-1=15y-13-2y | | y+(y-2)2=2 | | 3x-n=7+n | | 25-13=3(x-1) | | -13.9=b+17.1 | | r+7= | | 15-44=3(x-4)-5 | | 3x+(x-5)=15+4 | | -16+13=m-2 | | -3x=8-(-1) |